Extraction and Counter-Current Separation of Phenylpropanoid Glycosides from Pedicularis oederi Vahl by Deep Eutectic Solvent - Yao Wang; Jun Dai; Xiaoting Zhang; Yuhan Wang; Fangfang He; Lu Liang; Duojie Longzhu; Denglang Zou (Separations)
Deep eutectic solvents (DESs) are mixtures of organic compounds displaying excellent solvent properties while keeping an ecofriendly character. In this study, DESs have been applied to the extraction of phenylpropanoid glycosides from Pedicularis oederi Vahl, successively separated by means of counter-current chromatography. Firstly, the ultrasonic-assisted extraction conditions were optimized by response surface methodology, and the results showed phenylpropanoid glycosides could be well extracted under the optimized extraction conditions with deep eutectic solvents. Then, the sample was separated by counter-current chromatography using ethyl acetate/aqueous solution of choline chloride and glycerol (6:6, v/v) as the solvent system. In about 360 min, four phenylpropanoid glycosides, including 31.6 mg of echinacoside, 65.3 mg of Jionoside A1, 28.9 mg of Forsythoside B, 74.1 mg of verbascoside, and 21.2 mg of kaempferol-3-O-rutinoside were obtained from about 900 mg of the sample. It revealed deep eutectic solvents could be well employed as a green solvent for the extraction and counter-current separation of natural products.